Aspects of linguistic ageing in literary authors across time - Carmen Klaussner (Polish Academy of Sciences, 2021)
This work offers an investigation into linguistic changes in a corpus of literary authors hypothesised to be possibly attributable to the effects of ageing. In part, the analysis replicates an earlier study into these effects, but adds to it by explicitly analysing and modelling competing factors, specifically the influence of background language change. Our results suggest that it is likely that this underlying change in language usage is the primary force for the change observed in the linguistic variables that was previously attributed to linguistic ageing.